Mudanças nas transações entre produtores de verduras e grandes empresas supermercadistas: um estudo de caso - Bonfim, Renato Manzini (2011)
Leading supermarkets have developed the category of Fruits, Vegetables and Greens (FVG) as a strategy of differentiation. Some companies are promoting changes in the way they source, decreasing the spot market purchase and seeking greater proximity to the productive sector. In operational terms, is highlighted by the use of own distribution centers and tools for performance evaluation. Commercially, the strategy turns to direct relationships with farmers. This process has brought new demands for rural production: economies of scale and scope, regularity and quality of products, adoption of more efficient technologies of production, reorganization of suppliers, etc., especially for small and medium farmers. This process of change has been supported by an expansion of areas of contact, encouraging communication and exchange information, underpinned by the adoption of information systems. Existing studies of transactions between supermarket companies and producers don´t explore the dynamics of changes in transactions and governance relating them to advantages and disadvantages that they entail. Thus, the present work describes the changes in the supply of a large supermarket company, the reflections on the transactions and adjustments made in the structure of governance, while also addressing the advantages and disadvantages for the greens producers and for the company. Primary data were collected from interviews with the company and the suppliers of supermarket responsible for supply stores in São Paulo with fresh greens. Data were analyzed qualitatively. As a result, it was found that changes in the supply structure altered transactions and the organizational form adopted to coordinate them. The approach of the supermarket sector has enabled control over production, driving actions for improvement. For this, the company made use of training programs, auditing and performance tracking tools, elements necessary to supplement the contract that formalizes the transaction. Were found elements of hybrid governances, with predominance of strong leadership from the supermarket company in the adequacy of the productive sector, providing greater adaptability to the agents facing the demands of market. The adoption of a hybrid structure has brought advantages and disadvantages for agents. Access to market information and training programs were among the highlights advantages to the producer. The weakening of the supplier's trademark was a disadvantage identified. For the supermarket company, advantage in controlling the supply was identified. On the other hand, high cost of the control structure was the greater disadvantage. In the perception of agents, advantages outweigh disadvantages. The process of change involved selection of suppliers, excluding those who could not meet minimum requirements. However, informal organizational arrangements have been building among producers and have enabled the inclusion of other actors in the transactions. The study contradicts assumptions that the requirements imposed by supermarket companies are factors of exclusion of suppliers, and highlights its importance in driving positive change in the supply chain of fresh greens.